Volume 5C: Heat Transfer 2014
DOI: 10.1115/gt2014-25466
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady 360 CFD Validation of a Turbine Stage Mainstream/Disc Cavity Interaction

Abstract: The amount of cooling air assigned to seal high pressure turbine rim cavities is critical for performance as well as component life. Insufficient air leads to excessive hot annulus gas ingestion and its penetration deep into the cavity compromising disc or cover plate life. Excessive purge air, on the other hand, adversely affects performance. Experiments on a rotating turbine stage rig which included a rotor-stator forward disc cavity were performed at Arizona State University. The turbine rig has 22 vanes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They also observed that the cells dissipate at higher purge flow rates. A criticism by Mirzamoghadam et al was written claiming that the structures found may be a transient phenomenon that is caused by an insignificant number of revolutions of the rotor performed to resolve the case to a satisfactory solution [10].…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that the cells dissipate at higher purge flow rates. A criticism by Mirzamoghadam et al was written claiming that the structures found may be a transient phenomenon that is caused by an insignificant number of revolutions of the rotor performed to resolve the case to a satisfactory solution [10].…”
Section: Introductionmentioning
confidence: 99%
“…A rebuke by Mirzamoghadam et. al. was written claiming that the structures found may be a transient phenomenon that is caused by an insignificant number of revolutions of the rotor performed to resolve the case to a satisfactory solution [5].…”
Section: Introductionmentioning
confidence: 99%